2008 IEEE International Conference on Emerging Technologies and Factory Automation 2008
DOI: 10.1109/etfa.2008.4638455
|View full text |Cite
|
Sign up to set email alerts
|

A neural network multiagent architecture applied to fieldbus intelligent control

Abstract: This paper presents a multiagent architecture applied to factory automation. These agents detect faults in process automation and allocate intelligent algorithms in field device function blocks to solve these faults. It is also present a dynamic function block parameter exchange strategy which allows agent fieldbus allocation. The objective is to enable problem detection activities independent of user intervention. The use of Artificial Neural Network (ANN)-based algorithms enables the agents to learn about fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The test process contains portions that are similar to industrial processes. This environment was presented for the first time in our previous work [34] and the results were shown in [35]. Unlike these approaches, in this paper, we reexecute the examples using the LABVIEW-FIPA layer instead of the JADE-FIPA layer.…”
Section: B Multiagent Architecture Examplementioning
confidence: 91%
“…The test process contains portions that are similar to industrial processes. This environment was presented for the first time in our previous work [34] and the results were shown in [35]. Unlike these approaches, in this paper, we reexecute the examples using the LABVIEW-FIPA layer instead of the JADE-FIPA layer.…”
Section: B Multiagent Architecture Examplementioning
confidence: 91%
“…The test process contained parts that were similar to industrial processes. This environment was presented for the first time in our previous work (Machado et al, 2008a), and the results were showed in Machado et al (2008b). Table Exchange As we can see in Figure 14, the plant level is composed of two cascading tanks.…”
Section: Real Environment Examplementioning
confidence: 99%